2019
DOI: 10.1002/ange.201909511
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Cyanide or Isocyanide?

Abstract: Preference for the binding mode of the CN À ligand to Mg (Mg À CN vs.Mg À NC) is investigated. Amonomeric Mg complex with at erminal CN ligand was prepared using the dipyrromethene ligand Mes DPM which successfully blocks dimerization. While reaction of ( Mes DPM)MgN(SiMe 3 ) 2 with Me 3 SiCN gave the coordination complex ( Mes DPM)MgN-(SiMe 3 ) 2 ·NCSiMe 3 ,r eaction with ( Mes DPM)Mg(nBu) led to ( Mes DPM)MgNC·(THF) 2 .AM g À NC/Mg À CN ratio of % 95:5 was established by crystal-structure determination and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
2
0
0
Order By: Relevance
“…The single‐crystal X‐ray structural analyses showed that from the trinuclear N to the pentanuclear M , the cyanide bridge between silver and ruthenium turned around, namely the backbone is Fe‐(μ‐NC)‐Ru‐(μ‐NC)‐Ag‐(μ‐CN)‐Ru‐(μ‐CN)‐Fe not Fe‐(μ‐NC)‐Ru‐(μ‐CN)‐Ag‐(μ‐NC)‐Ru‐(μ‐CN)‐Fe, confirmed by their IR spectra and the following fact: during solving the single crystal structure, if the orientation of the bridging cyanide coordinated to ruthenium remained unchanged, the refinement would give much higher w R2 and R1 values, with unrealistically displacement parameter for both the C and N atoms. The similar phenomenon for this alternative cyanide connectivity was also reported by Harder et al [13] . This fact will be further discussed in the following section of Crystal structures.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The single‐crystal X‐ray structural analyses showed that from the trinuclear N to the pentanuclear M , the cyanide bridge between silver and ruthenium turned around, namely the backbone is Fe‐(μ‐NC)‐Ru‐(μ‐NC)‐Ag‐(μ‐CN)‐Ru‐(μ‐CN)‐Fe not Fe‐(μ‐NC)‐Ru‐(μ‐CN)‐Ag‐(μ‐NC)‐Ru‐(μ‐CN)‐Fe, confirmed by their IR spectra and the following fact: during solving the single crystal structure, if the orientation of the bridging cyanide coordinated to ruthenium remained unchanged, the refinement would give much higher w R2 and R1 values, with unrealistically displacement parameter for both the C and N atoms. The similar phenomenon for this alternative cyanide connectivity was also reported by Harder et al [13] . This fact will be further discussed in the following section of Crystal structures.…”
Section: Resultssupporting
confidence: 87%
“…confirmed by their IR spectra and the following fact: during solving the single crystal structure, if the orientation of the bridging cyanide coordinated to ruthenium remained unchanged, the refinement would give much higher wR2 and R1 values, with unrealistically displacement parameter for both the C and N atoms. The similar phenomenon for this alternative cyanide connectivity was also reported by Harder et al [13] This fact will be further discussed in the following section of Crystal structures.…”
Section: Synthesissupporting
confidence: 86%